2017
DOI: 10.26891/jik.v4i1.2010.30-35
|View full text |Cite
|
Sign up to set email alerts
|

Faktor-faktor yang Mempengaruhi Partisipasi Mahasiswa dalam Proses Tutorial pada Metode Belajar Problem-Based Learning (PBL) di Fakultas Kedokteran Universitas Riau

Abstract: Problem-based Learning (PBL) is an effective approach to promote student-centered learning. PBL tutorials were the key step in PBL process. Students' participation in PBL tutorials can be influenced by many factors. The aim of this study was to identify the factors that influence students' participation in PBL tutorials among students in Faculty of Medicine University of Riau. The research was a cross sectional study using self report questionnaires obtained from PBL students, conducted in April -October 2009.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
1
0
1
Order By: Relevance
“…They believed that the scenarios encouraged them to use literature related to the learning objectives. This result was consistent with Hamidy et al, who reported that a scenario was not correlated with the discussion process (25). Our result contradicted the findings of previous studies that a good scenario had a substantial effect on a PBL discussion (10,26).…”
Section: Scenario Quality and Effectiveness Of The Group Discussionsupporting
confidence: 89%
“…They believed that the scenarios encouraged them to use literature related to the learning objectives. This result was consistent with Hamidy et al, who reported that a scenario was not correlated with the discussion process (25). Our result contradicted the findings of previous studies that a good scenario had a substantial effect on a PBL discussion (10,26).…”
Section: Scenario Quality and Effectiveness Of The Group Discussionsupporting
confidence: 89%
“…Partisipasi mahasiswa dalam proses tutorial dapat dipengaruhi oleh beberapa faktor, antara lain karakteristik mahasiswa tersebut, kualitas skenario yang digunakan dan peranan tutor sebagai fasilitator. 3 Tutorial adalah proses belajar dengan bimbingan tutor kepada mahasiswa, yang bertujuan meningkatkan belajar mandiri mahasiswa.…”
Section: Pendahuluanunclassified
“…Several studies that compare scenario quality and PBL discussion, there was a study indicated a significant effect between scenario quality and the effectivity of PBL discussion in the School of Medicine, in which the better the scenario given to the students, the more effective the PBL discussion (Irgananda & Widodorini, 2017;Susanti et al, 2017). However, there was another study provided a contrast result, whereas the scenario was not correlated to the discussion process (Hamidy & Asni, 2017). Therefore, this study was conducted to investigate the correlation between scenario quality and the effectiveness of problem-based learning seven jumps discussion in medicine students of Mulawarman University.…”
Section: Introductionmentioning
confidence: 97%